The Quality of the Installation Service of Fish Seed (BBI) Trinsing in Fish Seed Suppliers in Barito Utara Districts - Mulyani, Fachrudin (TROPICAL WETLAND JOURNAL, 2018)
The research used descriptive qualitative method. Service was said to be of quality if the service received more than expected, satisfying if the service received the same as expected and if the service received less than expected, the service was said to be of low quality. The results show that the service quality provided by the Fisheries, Agriculture and Fisheries Department of North Barito Regency was considered satisfactory in terms of dimensions of responsiveness, dimensions of assurance and empathy. While the dimensions of reliability and dimensions of tangibles are considered unsatisfactory. Based on the results of the study, it is expected that the Fisheries, Fisheries and Animal Husbandry Department of North Barito Regency will be able to improve the quality of services by improving the quality of human resources and making new breakthroughs in fish farming technology.